Flexible La1.5Sr0.5NiO4/Poly(vinylidene fluoride) composites with an ultra high dielectric constant: A comparative study. (1st March 2020) - Meeporn, Keerati; Thongbai, Prasit
Abstract: Poly(vinylidene fluoride) (PVDF)–based polymer composites filled with high–permittivity La1.5 Sr0.5 NiO4 (LSNO) particles have been fabricated to produce a composite material with excellent dielectric performance and good mechanical flexibility. Micro–sized ( μ LSNO) and nano–sized LSNO ( n LSNO) particles are used separately as fillers. The dielectric properties of the composites are determined by their particle sizes, resultant interfacial area, and the interparticle distances between the LSNO particles. The percolation threshold of the n LSNO/PVDF composite is lower than that of the μ LSNO/PVDF composite. A greatly enhanced dielectric response with a high ε′ ≈ 565.9 at 1 kHz and room temperature and an effectively suppressed low loss tangent (tanδ ≈ 0.28) are obtained in the n LSNO/PVDF composite with a filler volume fraction of 30 vol %. The greatly enhanced ε′ value of n LSNO/PVDF can be explained by a combination of the interfacial polarization at the semiconducting n LSNO–insulating PVDF interfaces, an intrinsically giant ε′ response in n LSNO particles, and shorter interparticle distances between n LSNO particles in the PVDF matrix, while the retained low tanδ value is primarily attributed to the formation of a micro–capacitor microstructure.